An Effective Method Employing Alginate- TiO₂ Nanoparticles for Removing Bentazone Herbicide Residues from Water (Asian Journal of Pharmaceutics (AJP), 2024)
Our study explored the use of alginate-TiO₂ nanoparticles to effectively remove pesticide residues from water. Wesynthesized alginate-TiO₂ nanoparticles and characterized them using XRD, SEM, EDS, TEM, and FTIR. We thenevaluated their ability to degrade four common bentazone residues in aqueous solutions under various sunlightconditions. Sterile buffer water solutions (pH 4, 7, and 9) containing 1 mg/L bentazone were prepared in a singlereplicate and stored in clear glass bottles. The bottles were sealed, covered with aluminum foil, and kept in directsunlight. At periodically, the samples were tested for bentazone concentration using a validated HPLC method.On day 10, the photolysis test showed that 4.21%, 6.83%, and 15.28% of the bentazone had been hydrolyzed inthe pH-4, pH-7, and pH-9 buffers, respectively. On day 2, the photocatalysis test using nanocatalyst revealed that89.20%, 90.26%, and 97.12% of the bentazone were catalyzed, respectively. According to the findings, nanocatalystis an effective decontaminating agent for removing pesticide residues from water. Alginate-TiO₂ nanocatalystgives cost-effective, efficient, and environmentally friendly alternatives to traditional decontamination methods.Our study suggests that alginate-TiO₂ nanocatalyst is a promising nanomaterial for removing pesticide residuesfrom water, with potential applications in wastewater treatment and environmental remediation. We hope thatour findings will encourage further research on this issue and contribute to the development of sustainable andenvironmentally friendly solutions for enhancing water quality.